Pengaruh Kualitas Aset, Likuiditas, Rentabilitas Dan Efisiensi Operasional Terhadap Rasio Kecukupan Modal Pada Perusahaan Bank Konvensional Di Bursa Efek Indonesia Periode 2020-2023 - Bellanti, Silvan; Basalamah, Muhammad Ridwan; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This Study Aims To Examine The Influence Of Asset Quality, Liquidity, Profitability, And Operational Efficiency On The Capital Adequacy Ratio. The Population In This Study Consists Of Conventional Banks Listed On The Indonesia Stock Exchange. The Sampling Method Used In This Study Is Purposive Sampling, Which Involves Selecting Samples Based On Specific Criteria. This Study Includes 8 Banking Companies. Multiple Linear Analysis Is Used In This Research. The Results Of This Study Indicate That Asset Quality (NPL) Does Not Have A Significant Effect On The Capital Adequacy Ratio (CAR), Liquidity (Ldr) Has A Significant Effect On The Capital Adequacy Ratio (CAR), Profitability (Roa) Has A Significant Effect On The Capital Adequacy Ratio (CAR), And Operational Efficiency (Bopo) Has A Significant Effect On The Capital Adequacy Ratio (CAR) Keywords: Asset Quality, Liquidity, Profitability, Operational Efficiency, And Capital Adequacy Ratio